Analisis Trend Bisnis pada Jasa Laundry Cukling Di Jakarta Timur - Muhammad Yoga Pratama; Nur Fitri Rahmawati (JAMBIS : Jurnal Administrasi Bisnis, 2021)
This research is entitled Analysis of Business Trend of Jasa Laundry Cukling in East Jakarta. The purpose of this research is to find out and analyze the business trend of Jasa Laundry Cukling (a laundry service provider), increase the buying interest / selling power of Jasa Laundry Cukling, and determine the obstacles faced by Jasa Laundry Cukling and the efforts they make to overcome these obstacles. The data in the study were obtained through observation and interviews with 5 informants, and were analyzed using descriptive qualitative methods. Based on the results of the analysis, it can be concluded that the business trend analysis used by Jasa Laundry Cukling is very significant because it will have a positive impact on consumer buying interest. The obstacles that were found were the lack of technology utilization, low public knowledge about shoe laundry, and less than optimal promotion and innovation. Efforts that Jasa Laundry Cukling can do to increase consumer buying interest are collaborating with similar companies such as the Go-Clean app, adding payment instruments, innovating better, and always evaluating and analyzing market needs.